Barriers to Enrollment in Post-Stroke Brain Stimulation in a Racially and Ethnically Diverse Population. (September 2022) - Hodics, Timea; Cohen, Leonardo G.; Pezzullo, John C.; Kowalske, Karen; Dromerick, Alexander W.
Background and Purpose: Brain stimulation is an adjuvant strategy to promote rehabilitation after stroke. Here, we evaluated the influence of inclusion/exclusion criteria on enrollment in a transcranial direct current stimulation (tDCS) trial in the context of a racially/ethnically diverse acute stroke service at University of Texas Southwestern (UTSW). Methods: 3124 (59.7 ± 14.5 years) racially/ethnically diverse (38.4% non-Hispanic white, (W), Hispanic (H) 22%, African American (AA) 33.5%, Asian (A) 2.3%) patients were screened in the acute stroke service at UTSW. Demographics, stroke characteristics, and reasons for exclusion were recorded prospectively. Results: 2327 (74.5%) patients had a verified stroke. Only 44 of them (1.9%) were eligible. Causes for exclusion included in order of importance: (1) magnitude of upper extremity (UE) motor impairment, (2) prior strokes (s), (3) hemorrhagic stroke, (4) psychiatric condition or inability to follow instructions, and (5) old age, of these (2) and (4) were more common in AA patients but not in other minorities. 31 of the 44 eligible individuals were enrolled (W 1.68%, H 1.37%, AA .77%, A 3.774%). 90.5% of verified stroke patients did not exhibit contraindications for stimulation. Conclusions: 3 main conclusions emerged: (a) The main limitations for inclusion in brain stimulation trials of motor recovery were magnitude of UE motor impairments and stroke lesion characteristics, (b) most stroke patients could be stimulated with tDCS without safety concerns and (c) carefully tailored inclusion criteria could increase diversity in enrollment. Clinical Trial Registration-URL:http://clinicaltrials.gov . Unique identifier: NCT01007136.